Epidemiologic and public health initiatives in telecommunication Iniciativas epidemiológicas e de saúde pública nas telecomunicações - Pierre Philippe; R.E. Laporte; F. Sauer (Revista Brasileira de Epidemiologia, 1999)
Epidemiologic knowledge must be available widely in order to insure public health for all worldwide. The objective of this paper is to account for what has been done in epidemiologic telecommunication during the previous four years at the University of Montreal, and to discuss the future of telecommunication for public-health enhancement. The first step taken has been to set up a mailing list in methodological epidemiology. The second step has been the launching of a virtual seminar in theoretical epidemiology. It is advocated that virtuality is mandatory to disseminate public health information, but that several crucial issues must be solved before the objective can be reached, among them the cultural, political and ethical issues of the endeavor. This paper includes a critical appraisal of the consequences for under-developed countries of the worldwide telecommunication expansion in the field of public health. O conhecimento epidemiológico deve ser amplamente disponível para assegurar saúde pública para todos. O objetivo deste estudo é descrever o que tem sido realizado na área de telecomunicação epidemiológica na Universidade de Montreal, nos últimos quatro anos, e discutir as perspectivas do uso da telecomunicação no aprimoramento da saúde pública. Inicialmente foi criada uma mala direta de metodologia epidemiológica. A seguir, organizamos um seminário virtual de epidemiologia teórica. Tem se defendido que os recursos virtuais são indispensáveis para a disseminação da informação na área da saúde pública, entretanto, diversos pontos cruciais devem ser resolvidos antes que esse objetivo seja alcançado, entre eles aspectos culturais, políticos e éticos relacionados ao projeto. Este estudo apresenta uma análise crítica das conseqüências, para os países em desenvolvimento, da expansão da telecomunicação global na área da saúde pública.